The Influence of GSRS in Learning Basketball Game Activities on Students' Learning Experience - Triana Putri Nurharisa; Asep Sumpena; Marisa Noviyanti Fajrah Ilsya (Journal of Physical Education Health and Sport, 2025)
This study examines the impact of the application of Game based Student Response systems (GSRS) in basketball learning on student learning experience. Using a quasi-experimental design with the Pretest-Posstest One Group Design model, the study involved 34 7th grade students of State Junior High Schools 14 Bandung KU 12-13 years old who were selected through random sampling techniques. Data were collected using questionnaire instruments and analyzed using the Paired T-Test statistical test through SPSS version 26. The results showed a significant improvement in the students’ learning experience after the implementation of GSRS, with an average posttest score higher than the pretest (p<0.05). The increase can be seen in the aspects of active involvement, material understanding, and student learning motivation. The results of the study show that the implementation of GSRS has a positive and significant influence on students’ learning experience, which is reflected in increased grades and a more even distribution of abilities among students. These findings indicate that GSRS is an effective method in improving the quality of students’ learning experience in basketball learning. This research makes an important contribution to the development of physical education learning strategies that integrate digital technology, especially in the context of basketball learning at the junior high school level in effectively improving the quality of student learning experience. These findings provide implications for the development of physical education learning strategies that are more adaptive to the needs of the digital native generation in the future.